Biological and nutritive value of milk and dairy products in the human diet - Zokhida Tashboevna Norkulova; Hikmatullo Anvar ugli Normatov; Jamoliddin Zoir ugli Suyunov (Science and Education, 2025)
This paper examines the biological and nutritive value of milk and dairy products within the dietary patterns of the population of Uzbekistan. The role of traditional foods such as katyk, kurt, and suzma as key sources of protein, calcium, and vitamins is analyzed. Particular attention is given to modern consumption trends, regional differences, and the influence of socio-economic factors on the population’s access to essential nutrients. The paper also presents original research findings demonstrating the contribution of dairy products to meeting the daily requirements for critically important micro- and macronutrients.